The Influence of Product Quality and Museum Facilities on Visitor Satisfaction at the Sonobudoyo Museum Yogyakarta - Mia Wahyu Lestari; Uystka Hikmatul Kamiliyah NH (TOBA: Journal of Tourism, Hospitality, and Destination, 2025)
This study aims to determine the effect of Product Quality and Museum Facilities on visitor satisfaction. This study uses a descriptive quantitative method. In this study, two hypotheses are being tested. The variables used in this study consist of independent variables, namely Product Quality (X1) and Facilities (X2), and a dependent variable, namely Visitor Satisfaction (Y). The data analysis tool used is IBM SPSS Statistics Version 26, with the analysis method being multiple linear regression. The sampling method used was purposive sampling, with a sample size of 100 respondents who had visited the Sonobudoyo Museum in Yogyakarta. The results of this study indicate that product quality significantly influences visitor satisfaction, while museum facilities do not significantly influence visitor satisfaction at the Sonobudoyo Museum in Yogyakarta. However, even though the facility aspect does not have a significant effect, it does not mean it can be ignored. Therefore, this study recommends that the Sonobudoyo Museum focus on improving and evaluating these aspects, especially the facility aspect, to create a better and more memorable cultural and historical tourism experience.